Respuesta :

Answer:

2nd option

Step-by-step explanation:

[tex]\frac{\sqrt{2} }{3}[/tex] r + 1 = 23 ( subtract 1 from both sides )

[tex]\frac{\sqrt{2} }{3}[/tex] r = 22 ( multiply both sides by 3 to clear the fraction )

[tex]\sqrt{2}[/tex] r = 66 ( divide both sides by [tex]\sqrt{2}[/tex] )

r = [tex]\frac{66}{\sqrt{2} }[/tex] × [tex]\frac{\sqrt{2} }{\sqrt{2} }[/tex] ( rationalising the denominator )

r = [tex]\frac{66\sqrt{2} }{2}[/tex] = 33[tex]\sqrt{2}[/tex]

Answer:

B) r=33*sqrt(2)

Step-by-step explanation:

sqrt(2)/3r+1=23

sqrt(2)/3r=23-1

sqrt(2)/3r=22

sqrt(2)r=22*3

sqrt(2)r=66

r=66/sqrt(2)

r=66*sqrt(2)/(sqrt(2)*sqrt(2))

r=(66*sqrt(2)/2

r=33*sqrt(2)